Critical success factors in ID 179 special projects a multiple-case study - Añonuevo, Maria Ivanka B. (College of Home Economics, University of the Philippines Diliman, 2023)
Over the past 20 years, the UP BS Interior Design Program has integrated the capstone course ID 179 “Special Project for Interior Design” which involved the rehabilitation of institutions whose interior spaces are run-down and neglected. However, since 2018, four out of five projects were not delivered on time -- a failure in one of the criteria of project success. With this, the study sought to identify the Critical Success Factors (CSF) that should be considered and successfully executed by project teams during the implementation of ID 179 Special Projects in order to successfully deliver projects on time. The researcher conducted a multiple-case study research design, analyzing two purposively selected completed projects—one finished on time and the other delayed. Qualitative data were gathered through surveys and interviews to shed light on the factors that students think were critical to a favorable outcome. The interviews provided supplementary information and evidence on the results of the survey. Using descriptive statistics, tabulation, and Directed Qualitative Content Analysis, the researcher summarized individual cases and drew cross-case conclusions. The findings indicate that Batch 2018 generally performed better than Batch 2023 in terms of successfully executing the Critical Success Factors. The students' performance on the CSF aligns with their assessment of project outcomes, supporting the theory that considering success factors increases the chances of project success. Furthermore, the study suggests that the CSF identified through literature review, together with the other factors that emerged in the study, are highly relevant to ID 179 Special Projects and can be used to evaluate future projects.